Application Value of STOP-Bang Questionnaire in Predicting Abnormal Metabolites - Pang Q; Han L; Li J; Xu L; Wang Y (Diabetes, Metabolic Syndrome and Obesity, 2025)
Qingyi Pang,1 Li Han,1 Jun Li,2 Lingling Xu,1 Yueheng Wang3 1Department of Endocrinology, Peking Union Medical College Hospital, Beijing, People’s Republic of China; 2Department of Endocrinology, Beijing Hepingli Hospital, Beijing, People’s Republic of China; 3Department of Ear, Nose and Throat, Beijing Hepingli Hospital, Beijing, People’s Republic of ChinaCorrespondence: Lingling Xu; Yueheng Wang, Email llxush@163.com; 8108374@qq.comObjective: To evaluate the application value of STOP-Bang questionnaire (SBQ) in predicting abnormal metabolites.Methods: Totally 121 patients were included into the study and filled the questionnaires, and their clinical data were collected at the same time. These patients were grouped according to the questionnaire scores. The clinical data of patients in various groups were compared using R4.3.1 statistical software.Results: Based on the SBQ score, the patients were divided into the following groups: low-risk group (0– 2 scores), mid-risk group (3– 4 scores), and high-risk group (5– 8 scores). SBQ score was related to several abnormal metabolites. A higher SBQ score indicated elevated uric acid (UA), waist circumference (WC), fasting blood glucose (FBG), hemoglobin A1c (HbA1c) and triacylglycerol (TG), but notably lower high density lipoprotein-cholesterol (HDL-C). In respect of liver function, alanine aminotransferase (ALT) and aspartate transaminase (AST) were both in low/mid-risk group than in high-risk group. With respect to renal function, there was a statistically significant difference in serum creatinine (SCr) (lowest in the low-risk group and highest in the high-risk group) but no such difference in estimated glomerular filtration rate (eGFR) among the three groups. The diagnosability analysis showed that the AUROC proved the good performance of SBQ in predicting metabolic syndrome (MetS) and hyperuricemia (HUA).Conclusion: OSA frequently co-occurs with various metabolic disorders. SBQ, a widely used tool for assessing the risk of OSA, may also be a potential tool for predicting the presence of metabolic diseases. A higher SBQ score indicates a heightened susceptibility to more abnormal metabolites, but SBQ is poor in predicting liver and renal functions. The patients with SBQ score ≥ 3 are suggested to pay a visit to the Endocrine Department and Sleep Disorders Center for a comprehensive evaluation of comorbid Obstructive sleep apnea (OSA) and the management of systematic metabolism.Keywords: STOP-Bang questionnaire, metabolic syndrome, hyperuricemia, obstructive sleep apnea, OSA, health management